2005
DOI: 10.1097/01.rhu.0000191194.39926.c9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intraarticular Injection of Depot Corticosteroid and Hyaluronic Acid for Treatment of Degenerative Trapeziometacarpal Joints

Abstract: Steroids and hyaluronate injections were found effective in reducing pain. Hyaluronate was more effective in the improvement of some aspects of fine hand function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 11 publications
1
97
0
13
Order By: Relevance
“…A preliminary small study in 16 patients with OA in the trapeziometacarpal joint showed reductions in pain (maximal at 5 months) with 5 weekly injections of intra-articular HA [76]. Among subsequent randomised studies in similar populations, one in 52 patients showed that both HA and corticosteroid treatment were effective in reducing pain, although HA was more effective in improving some fine hand functions for up to 6 months [77]. Although one open-label study in 40 female patients with trapeziometacarpal joint OA showed corticosteroid treatment was superior to 3 weekly injections of HA in reducing pain and improving hand function [78], another randomised study in which 56 patients received 3 weekly intra-articular injections showed maximum pain relief at week 2 or 3 with steroid treatment, and at week 26 with HA which thus showed superior long-term improvements [79].…”
Section: Other Jointsmentioning
confidence: 99%
“…A preliminary small study in 16 patients with OA in the trapeziometacarpal joint showed reductions in pain (maximal at 5 months) with 5 weekly injections of intra-articular HA [76]. Among subsequent randomised studies in similar populations, one in 52 patients showed that both HA and corticosteroid treatment were effective in reducing pain, although HA was more effective in improving some fine hand functions for up to 6 months [77]. Although one open-label study in 40 female patients with trapeziometacarpal joint OA showed corticosteroid treatment was superior to 3 weekly injections of HA in reducing pain and improving hand function [78], another randomised study in which 56 patients received 3 weekly intra-articular injections showed maximum pain relief at week 2 or 3 with steroid treatment, and at week 26 with HA which thus showed superior long-term improvements [79].…”
Section: Other Jointsmentioning
confidence: 99%
“…The four RCTs [2,11,20,30] are considered first because they provide more powerful level 1b evidence [21]. The other five studies [5,13,15,17,32] are prospective case series, providing only level 4 evidence [23].…”
Section: Critical Appraisalmentioning
confidence: 99%
“…Beside pain reduction, also grip strength improved significantly in some studies (Migliore et al, 2010), although these effects were achieved slowly, with better results observed at 6 months (Fuchs et al, 2006;Heyworth et al, 2008;Stahl et al, 2005). In our experience (Table 4), a single ultrasound guided injection of hyaluronic acid is effective in treatment of carpo -metacarpal osteoarthritis (Salini et al, 2009).…”
Section: Carpo -Metacarpal Osteoarthritismentioning
confidence: 76%
“…Several conservative treatments have been proposed (corticosteroids, non steroidal antiinflammatory drugs, prolotherapy, splinting), but none of these has shown to delay the progression of osteoarthritis or reverse joint damage (Fuchs et al, 2006). In particular, an early improvement in Visual Analogic Scale score was observed after 2 weeks post treatment (Heyworth et al, 2008), with the effects lasting until 1 -3 months (Coaccioli et al, 2006;Roux et al, 2007;Schumacher et al, 2004;Stahl et al, 2005). The long term effects of hyaluronan were demonstrated only in few studies (Fuchs et al, 2006;Heyworth et al, 2008;), in which the pain relief was reported at 6 months (Di Sante et al, 2011).…”
Section: Carpo -Metacarpal Osteoarthritismentioning
confidence: 99%